Teman TOGA (Terapi Mandiri Tanaman Obat Keluarga) Community: Mengenal Kearifan Pengobatan Tradisional Indonesia dan Terampil Meracik Tanaman Obat: Teman TOGA (Terapi Mandiri Tanaman Obat Keluarga) Community: Get to Know the Wisdom of Indonesia Traditional Medicine and Be Skilled in Making Medicinal Plants - Ariyani, Herda; Muthaharah, Mustika; Nugraha, Tyas Setia; Saad , Zahra; Ahyati, Luthfia Raisah; Maulida, Sindy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Adolescents must be equipped with knowledge and skills to create health products based on local medicinal plants. Currently, Indonesian youth—especially those living abroad—tend to have a limited understanding of Indonesia's native medicinal plants, despite the country's rich and abundant biodiversity. This educational initiative aims to inform teenagers about traditional medicine and provide hands-on experience preparing and formulating TOGA (Family Medicinal Plants). The community service program employed methods such as online socialization and demonstrations on making instant ginger drinks and antiseptic betel leaf soap, with 23 participants. The results showed a significant improvement in knowledge, with the average pre-test score of 5.30 increasing to 8.35 in the post-test. A paired sample t-test yielded a p-value of 0.000 (<0.05), indicating a significant difference after the intervention. The correlation value of 0.612 suggests a moderately strong relationship between the intervention and the increase in scores, reinforcing the relevance of this educational effort in enhancing students' knowledge.